Key Reasons Behind the Success of Netflix - Miškóciová, Simona (2022)
This thesis investigates the success of Netflix. The goal is to define and describe the most important aspects, as well as steps that have led to the extraordinary growth of this company and to prove that Netflix is in fact a successful company. Researched topics include global expansion, original content creation, customer treatment, business culture, corporate social responsibility, and business viability. The main focus is on explaining and describing the global expansion strategy Netflix used in relation with content production, while applying theory like PESTLE Analysis or Modes of Entry to foreign markets. Moreover, big emphasis is put on investigating the customer satisfaction and preferences by collecting data from real Netflix users. The overall purpose of this thesis is to provide a deeper understanding and insights of Netflix and other Video on Demand providers for someone that might be a user of these streaming services.